Study of the anticoagulant activity of Rosa Damascena extract in vitro - احمد, علاء; نعمى حسن; ديمة الدياب (Latakia University Journal -Medical Sciences Series, 2023)
Rosa damascena is a phenols-rich plant with variable pharmacological effects. Despite the well-known anticoagulant properties of phenolic compounds, the anticoagulant effect of R. Damascena has not been investigated yet. Our study aimed to investigate the anticoagulant activity of aqueous R. damascena petals extracts, by testing its effect in vitro on prothrombin time PT using plasma from healthy adults and patients taking warfarin. Two aqueous extracts were prepared in two different ways. The total phenolic content of the two extracts were 32.23 g/L and 1.120 g/L. Different concentrations were prepared to test their effect on PT on plasma from both healthy adults and patients taking warfarin. All tested concentrations showed a significant prolongation of PT compared to the blank and the effect was concentration- dependent. The EC50 of extracts tested on plasma of warfarin patients (1110.374 mcg/mL) was lower than the EC50 of extracts tested on plasma of healthy adults (1137.354 mcg/mL). The results indicate a possible anticoagulant effect of aqueous R. damascena petals extracts. This effect might be synergistic to the effect of warfarin.